2016
DOI: 10.1007/s11999-016-4921-1
|View full text |Cite
|
Sign up to set email alerts
|

Hip, Knee, and Ankle Osteoarthritis Negatively Affects Mechanical Energy Exchange

Abstract: Background Individuals with osteoarthritis (OA) of the lower limb find normal locomotion tiring compared with individuals without OA, possibly because OA of any lower limb joint changes limb mechanics and may disrupt transfer of potential and kinetic energy of the center of mass during walking, resulting in increased locomotor costs. Although recovery has been explored in asymptomatic individuals and in some patient populations, the effect of changes in these gait parameters on center of mass movements and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…Comparisons to the literature suggest that reduced mechanical energy exchange was seen for the hip osteoarthritis patients compared to normal . THR participants in our study had a mechanical energy exchange that was similar to the hip osteoarthritis group reported by Queen et al ( R =54.0±10.0%), and significantly lower than the asymptomatic group in that study ( R =65.0±3.0%). Low mechanical energy exchange may increase the muscular effort to accelerate and decelerate the COM.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Comparisons to the literature suggest that reduced mechanical energy exchange was seen for the hip osteoarthritis patients compared to normal . THR participants in our study had a mechanical energy exchange that was similar to the hip osteoarthritis group reported by Queen et al ( R =54.0±10.0%), and significantly lower than the asymptomatic group in that study ( R =65.0±3.0%). Low mechanical energy exchange may increase the muscular effort to accelerate and decelerate the COM.…”
Section: Discussionsupporting
confidence: 79%
“…We cannot confirm whether or not the result in the THR patients would be different than that in healthy subjects. However, we note that the mechanical energy exchange was lower than that seen in the control sample of Queen's study . Finally, the cross‐sectional study design precludes inferring causation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As specialists note [27,30,31,35] knee pain when ascending staircase or walking on even inclined surfaces is an evident factor, limiting physical activity with OA of knee joint. It is proved also be the data of other scientists [64,69,70]. The authors found that it is tiresome for people with lower limbs' OA to fulfill ordinary movements, because joint changes can block transition of potential and kinetic energy of mass centers during walking.…”
mentioning
confidence: 76%